2012
DOI: 10.7710/2162-3309.1050
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Making Use of Academic Authors’ Open Access Rights

Abstract: INTRODUCTION Authors of academic works do not take full advantage of the self-archiving rights that they retain in their publications, though research shows that many academic authors are well-aligned (at least in principle) with open access (OA) principles. This article explains how institutionally-assisted self-archiving in open access repositories can effectively take advantage of retained rights and highlights at least one method of facilitating this process through automated means. METHODS To understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Estimates have put that percentage in the range of 11 67 to 29 percent. 68 Although we did not assess whether the publisher PDFs were permitted for our sample, other studies have found that posted PDFs generally were not permitted. 69…”
Section: Discussionmentioning
confidence: 99%
“…Estimates have put that percentage in the range of 11 67 to 29 percent. 68 Although we did not assess whether the publisher PDFs were permitted for our sample, other studies have found that posted PDFs generally were not permitted. 69…”
Section: Discussionmentioning
confidence: 99%
“…However, not all versions of publications are permitted to be downloaded into repositories, but pre and post-prints are allowed by many publishers. In some cases, published articles in pdf format can be submitted to open access repositories or other venues by paying a high fee to the publisher (Hansen 2012). Peroni and co-authors cite studies showing that OA allows discoverability for research articles and datasets "made publicly available increase citation rates of article between 9% and 30%" (2015).…”
mentioning
confidence: 99%
“…3 The current study is a follow-up to this study, but concentrates on journal publications in order to provide an evaluation of all three tools in the workflow, as SHERPA/RoMEO's and Unpaywall's services are geared towards journal articles. (Table 2) (Abad-García et al, 2013;Covey, 2009;Fathli et al, 2014;Hansen, 2012;Jamali, 2016;Lyons & Booth, 2011;Walters & Daley, 2018). If eliminating the highest and lowest percentages, the range of journals without clear policies in SHERPA/RoMEO is closer to 10.0% to 15.0%.…”
Section: Zotero and Reference Management Softwarementioning
confidence: 97%